Penerapan Model Learning Cycle 5e dalam Materi Besaran Pokok dan Turunan di Kelas VII SMP Negeri 1 Sengah Temila - Sari, Ira Nofita; Saputri, Dwi Fajar; Beno, Yupensius (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2016)
This study aims to determine the application model of  learning cycle 5e on the magnitude and derivative material class VII SMP Negeri 1 Sengah Temila. This research was quasi experiment design with posttest only design control. Data collection tool used is a multiple choice test. The hypothesis was tested using the t test of the parties. Based on the analysis concluded that: (1) student learning outcomes after application model of learning cycle 5e on the material of magnitude and derivative class VII SMP Negeri 1 Sengah Temila classified as good, (2) student learning outcomes after application of the model learning cycle 5e on material of magnitude and derivative class VII SMP Negeri 1 Sengah Temila relatively less, and (3) the results of student learning after the applied model of learning cycle 5e better than student learning outcomes after applied of conventional learning models on the material of magnitude and derivative class VII SMP Negeri 1 Sengah Temila.Penelitian ini bertujuan untuk mengetahui penerapan model learning cycle 5 e pada materi besaran pokok dan turunan kelas VII SMP Negeri 1 Sengah Temila. Penelitian ini termasuk penelitian quasi eksperiment dengan rancangan posttest only design control design. Alat pengumpul data yang digunakan adalah tes pilihan jamak. Hipotesis diuji menggunakanuji t satu pihak. Berdasarkan hasil analisis data disimpulkan bahwa: (1) hasil belajar siswa setelah diterapkan model learning cycle 5 e pada materi besaran pokok dan turunan kelas VII SMP Negeri 1 Sengah Temilatergolong baik, (2) hasil belajar siswa setelah diterapkan model learning cycle 5 e pada materi besaran pokok dan turunan kelas VII SMP Negeri 1 Sengah Temilatergolong kurang, dan (3) hasil belajar siswa setelah diterapkan model learning cycle 5 e lebih baik daripada hasil belajar siswa setelah diterapkan model pembelajaran konvensional pada materi besaran pokok dan turunan kelas VII SMP Negeri 1 Sengah Temila.